2015
DOI: 10.1093/ofid/ofv079
|View full text |Cite
|
Sign up to set email alerts
|

CD4 Response Up to 5 Years After Combination Antiretroviral Therapy in Human Immunodeficiency Virus-Infected Patients in Latin America and the Caribbean

Abstract: We describe CD4 counts at 6-month intervals for 5 years after combination antiretroviral therapy initiation among 12 879 antiretroviral-naive human immunodeficiency virus-infected adults from Latin America and the Caribbean. Median CD4 counts increased from 154 cells/mm3 at baseline (interquartile range [IQR], 60–251) to 413 cells/mm3 (IQR, 234–598) by year 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
1
3
0
Order By: Relevance
“…Patients with a CD4 + T-cell count <200 cells/µl at the start of treatment had poorer immunologic outcomes than patients with >200 cells/ µl, consistent with the findings of previous studies (Garcia et al, 2004). In this study, most patients had high CD4 + T-cell counts at baseline, higher than those for patients on second-line ART in other studies (Luz et al, 2015), but similar to those reported in another study assessing LPV/r-based second-line ART (Patel et al, 2013). In an Iranian study, the authors reported that mean CD4 + T-cell counts had increased by 139 cells/µl relative to baseline at 12 months (Rasooli-Nejad et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Patients with a CD4 + T-cell count <200 cells/µl at the start of treatment had poorer immunologic outcomes than patients with >200 cells/ µl, consistent with the findings of previous studies (Garcia et al, 2004). In this study, most patients had high CD4 + T-cell counts at baseline, higher than those for patients on second-line ART in other studies (Luz et al, 2015), but similar to those reported in another study assessing LPV/r-based second-line ART (Patel et al, 2013). In an Iranian study, the authors reported that mean CD4 + T-cell counts had increased by 139 cells/µl relative to baseline at 12 months (Rasooli-Nejad et al, 2017).…”
Section: Discussionsupporting
confidence: 90%
“…Patients who died prior to each time point were assigned to have the worst rank measurements (i.e. the lowest CD4 measurement) [24,25]. The probability of a missing value was modelled separately for each laboratory measurement at each time point using logistic regression models that included covariates for site, age, sex, presence of AIDS-defining illness, year of ART initiation, ART regimen, probable route of HIV transmission and the corresponding baseline laboratory measurement.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the factors mentioned above, older age, male sex, lower nadir CD4 T‐cell counts, lower CD4/CD8 ratios, and a lower naïve/memory CD4 + T‐cell ratio have been associated with a blunted immunological response to ART treatment. Ethnic origin is also associated with immune recovery . Furthermore, host genetic factors, metabolic characteristics, and specific ART regimens may play a role in incomplete immune recovery.…”
Section: Potential Mechanisms Of Incomplete Immune Reconstitutionmentioning
confidence: 99%
“…Ethnic origin is also associated with immune recovery. [171][172][173][174] Furthermore, host genetic factors, metabolic characteristics, and specific ART regimens may play a role in incomplete immune recovery. Luo…”
Section: Other Factors Associated With Immune Reconstitutionmentioning
confidence: 99%